2021
DOI: 10.1002/ajoc.202100363
|View full text |Cite
|
Sign up to set email alerts
|

Formal [4+1] Cyclization of ortho‐ or para‐Quinone Methides with 3‐Chlorooxindoles: Synthesis of 3,2′‐Tetrahydrofuryl Spirooxindoles

Abstract: A base promoted formal [4+1] cycloaddition of ortho‐ and para‐quinone methides with 3‐chlorooxindoles is reported to afford various functionalized 3,2′‐tetrahydrofuryl spirooxindoles in high yields under mild conditions. An unexpected reversal in diastereoselectivity was observed from these two types of reactions. Computational studies have provided insight into the origin of diastereoselection, and different configurations of 1,4‐addition and 1,6‐addition at the oxindole carbanionic center are found to give r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The employment of organic and inorganic bases as catalysts or reagents for the green synthesis of organic molecules has been an active area of research and development. We here list recent progress in base-promoted reactions for the synthesis of spirooxindoles, using caesium carbonate, 30 triethyl amine, 30 potassium fluoride, 31 and calcium hydroxide. 32…”
Section: Non-chiral Pathways To Spirooxindole Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The employment of organic and inorganic bases as catalysts or reagents for the green synthesis of organic molecules has been an active area of research and development. We here list recent progress in base-promoted reactions for the synthesis of spirooxindoles, using caesium carbonate, 30 triethyl amine, 30 potassium fluoride, 31 and calcium hydroxide. 32…”
Section: Non-chiral Pathways To Spirooxindole Frameworkmentioning
confidence: 99%
“…Tian et al reported a base-promoted [4 + 1]-cycloaddition of ortho - and para -quinone methides (Schemes 13 and 14) with 3-chlorooxindoles to furnish substituted 3,2′-tetrahydrofuryl spirooxindoles in high yields and moderate diastereoselectivities. 30 Initially 2-sulfonlalkyl phenols 18 were reacted with 3-chlorooxindoles 20 to form spirooxindoles 21 in quantitative yields. The unprotected N–H amide furnished low yields and modest diastereoselectivity (Scheme 13).…”
Section: Non-chiral Pathways To Spirooxindole Frameworkmentioning
confidence: 99%